Motivasi Belajar sebagai Prediktor Hasil Belajar Bola Voli dalam Pendidikan Jasmani: Sebuah Studi di SMP IT Al Azhar 24 - Irfan Zinat Achmad; Tedi Purbangkara; Dhika Bayu Mahardhika; Ruslan Abdul Gani; Alam Hadi Kosasih (Indonesian Journal of Physical Education and Sport Science, 2026)
Study Purpose This study aimed to examine the relationship between students’ motivation and learning outcomes in volleyball learning at SMP TI Al Azhar 24. Materials and Methods A quantitative correlational design was used with a sample of 60 students from grades VII to IX. Motivation data were collected using a questionnaire grounded in Self-Determination Theory, while volleyball learning outcomes were measured using a test assessing both technical performance and theoretical understanding. Data were analyzed using Pearson Product–Moment correlation and simple linear regression. Results The mean motivation score was 96.83 and the mean volleyball learning outcome score was 82.57, indicating generally moderate to high levels of motivation and achievement. The analysis showed a strong, positive relationship between motivation and learning outcomes (r = 0.674; p < 0.05). Regression results indicated that motivation explained 45.4% of the variance in volleyball learning outcomes, with the remaining variance attributed to other factors. Conclusion Motivation is strongly associated with volleyball learning outcomes in physical education. Teachers are encouraged to build supportive and enjoyable learning environments that strengthen students’ intrinsic motivation and engagement during volleyball instruction.